The System of Principles in Teaching Informatics as A Factor Determining the Content in Educational Practice - Dilfuza Melievna Makhmudova (Genius Journals, 2022)
The modular principle of teaching is widely applied for the training of specialists in the sphere of higher education. It is based on the principles of science and consistency. A set of new method and theses, which are united by a common idea, enables us to speak about an innovational technology of modular teaching of informatics. In this article we consider application of principles of science and consistency for modular technology of teaching of mathematics.
Keywords: System of principles; principles of education; modular system of education